Remarks on what we are looking for - Sofie Podlipská in the context of fin de siècle thoughts - Vrajová, Jana (Bohemica Olomucensia, 2013)
The authors inteprets Podlipská's remarks as the evidence of changes in mentality of well-educated writer at the end of 19th century. Podlipská's remarks were probably an attempt to reformulate the crucial questions of human existence, to utilize the alternative ways of thinking and to review the previous knowledge.